Management styles of Malaysian managers a cross-cultural perspective - Syed Azizi Wafa Syed Khalid Wafa (Inaugural lecture series, 2014)
This book will lead to a better understanding towards how these management styles have led to the success and failures of companies and individuals and hep us to better organize and strategize ourselves for the future